Delay determinants of European Banking Union implementation - Michael Koetter; Thomas Krause; Lena Tonzer (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2017)
To safeguard financial stability and harmonise regulation, the European Commission substantially reformed banking supervision, resolution, and deposit insurance via EU directives. But most countries delay the transposition of these directives. We ask if transposition delays result from strategic considerations of governments conditional on the state of their financial, regulatory, and political systems? Supervisors might try to protect national banking systems and local politicians maybe reluctant to surrender national sovereignty to deal with failed banks. Alternatively, intricate financial regulation might require more implementation time in large and complex financial and political systems. We therefore collect data on the transposition delays of the three Banking Union directives and investigate observed delay variation across member states. Our correlation analyses suggest that existing regulatory and institutional frameworks, rather than banking market structure or political factors, matter for transposition delays.
urn:nbn:de:gbv:3:2-81552
Keywords: C41; F30; F55; G15; G18; 330; single rulebook; political economy; transposition delays